2023
DOI: 10.1097/htr.0000000000000829
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Deaths by Suicide, Drug Overdose, and Opioid-Related Overdose in a National Sample of Military Members With Mild Traumatic Brain Injury, 1999-2019

Abstract: Objective: To examine racial and ethnic differences in suicide and drug and opioid-related overdose deaths among a population-based cohort of military service members who were diagnosed with a mild traumatic brain injury (mTBI) during military service. Design: Retrospective cohort. Setting: Military personnel receiving care within the Military Health System between 1999 and 2019. Participants: In total, 356 514 military members aged 18 to 64 years, who received an mTBI diagnosis as their index TBI betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although findings presented add to evidence of disparities in TBI care and outcomes across SDoH, what continues to be urgently needed is empirical support for purported theories explaining such disparities—many of which were advanced by authors of studies included in this issue. For example, several studies revealed racial disparities in TBI care and outcomes 7,8,10,11. However, race and ethnicity are socially constructed categories that serve as surrogate measures of historical and structural marginalization that may shape TBI care and recovery in myriad, dynamic, and mutually reinforcing ways 20.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although findings presented add to evidence of disparities in TBI care and outcomes across SDoH, what continues to be urgently needed is empirical support for purported theories explaining such disparities—many of which were advanced by authors of studies included in this issue. For example, several studies revealed racial disparities in TBI care and outcomes 7,8,10,11. However, race and ethnicity are socially constructed categories that serve as surrogate measures of historical and structural marginalization that may shape TBI care and recovery in myriad, dynamic, and mutually reinforcing ways 20.…”
Section: Future Directionsmentioning
confidence: 99%
“…Several studies in this issue document disparities in TBI care and outcomes among members of marginalized racial and ethnic groups. Bahraini et al 7 conducted a population-based study of military members with mild traumatic brain injury (mTBI) to examine potential racial and ethnic disparities in mortality risk. Their data indicated that risk for death by suicide, drug overdose, and opioid overdose was substantially higher among military members who self-identified as "other," a racial category that may reflect minoritized individuals whose self-conception of racial identity is outside the bounds of standard categories (eg, multiracial).…”
Section: Racial Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation